A Contribution to Anatolian-Turkish Urban History: The Anatolian Seljuk City (From the Beginning of the 12th Century to the End of the 13th Century) - Ozcan, Koray; Yenen, Zekiye (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
Anatolian Seljuk cities reflect the morphological characteristics in terms of their spatial and functional roles in the urban network and transportation system set up in Anatolia. Within this scope of definition, (the meaning of) the concept of the Anatolian Seljuk city is conceived as the result of the impact of the social, cultural and economic symbiosis between Christian-Byzantine and Muslim-Seljuk on spatial organization in Anatolia. In order to establish the Anatolian Seljuk city, in terms of research sources and its methodology, it is considered that the use of original historical and manuscript sources and their spatial dimension should be used. Within this framework, the spatial organization and morphologies of Anatolian Seljuk cities are defined using maps based on manuscript sources and archaeological or architectural ruins. As a result, Anatolian Seljuk cities developed based on Byzantine urban heritage, and also organized spatially under the impact of pre-Anatolian Turkish urban culture. In this regard, three categories were defined, namely fortified city, open city and external focused city models, according to their distinguishing spatial and functional characteristics.
Keywords: Anatolia; urban models; Seljuk; the Anatolian Seljuk city; Architecture